Airborne Microorganisms in Commercial Shell Egg Processing Facilities - Northcutt, J.K.; Jones, D.R.; Ingram, K.D.; Hinton, A.; Jr.; Musgrove, M.T. (International Journal of Poultry Science, 2004)
Total aerobic bacteria, molds/yeasts, coliforms and pseudomonads in the air in three shell egg processing operations (in-line, off-line and mixed operations) were determined using MicroBio MB2 Air Samplers. Sites were sampled from each facility on three different days (replication) during the same week. Four air samples (1000 L each) were drawn from each sampling site on a given day. Sampling sites, included areas in or near the following on-site locations: hen house (in-line and mixed operations), farm transition room (in-line and mixed operations), egg washers, egg dryer, packer heads, post-processing cooler, nest-run cooler (off-line and mixed operations), loading dock and dry storage. Type of operation (in-line, off-line or mixed), sampling site and the interaction between operation and site had a significant effect on the number of total aerobic bacteria, molds/yeasts, coliforms and pseudomonads recovered (P < 0.05). Highest counts for total aerobic bacteria (5.9 log10 cfu/ml air), molds/yeasts (4.0 log10 cfu/ml air) and coliforms (2.5 log10 cfu/ml air) were found in the hen house. Highest counts for pseudomonads were found in the hen house (3.2 log10 cfu/ml air) and behind the egg washer (3.5 log10 cfu/ml air). Lowest counts for total aerobic bacteria (2.5 log10 cfu/ml air) and molds/yeast (2.7 log10 cfu/ml air) were found in the post-processing cooler. Few samples in the post-processing coolers, nest-run coolers, loading docks and dry storage areas tested positive for coliforms (0/36, 2/24, 1/36 and 0/36, respectively) and pseudomonads (1/36, 2/24, 5/36 and 6/36, respectively). Data gathered during this study has been useful in identifying the sources and levels of airborne contaminates in commercial shell egg processing facilities.